Conducting the Needs Assessment #6: Phase 2 – Assessment - Matt Benge; Savanna Turner (EDIS)
This is the sixth publication in the Conducting the Needs Assessment series. The assessment phase puts the management plan from the pre-assessment into action to determine the needs of your community. The assessment phase compares the “what is” of the issues to the vision of the “what should be” to understand the magnitude of the needs and their causes (Witkin & Altschuld, 1995).